2014
DOI: 10.1007/s13300-014-0064-0
|View full text |Cite
|
Sign up to set email alerts
|

Use of Vildagliptin in Management of Type 2 Diabetes: Effectiveness, Treatment Persistence and Safety from the 2-Year Real-Life VILDA Study

Abstract: IntroductionThere is an increasing interest for real-life data on drug use in many countries. Reimbursement authorities more and more request observational studies to assess the conditions of use of the products but also to improve knowledge about efficacy and safety in the real world and on a longer term than in clinical trials.AimTo evaluate the effectiveness, treatment persistence and tolerability of vildagliptin in clinical practice.MethodsThis observational, 2-year prospective cohort study was conducted i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
5
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 48 publications
5
5
0
Order By: Relevance
“…However, data on HbA 1c were missing for a significant minority of patients, which means that these data should be interpreted with caution. The efficacy of sitagliptin observed in our study is similar to the efficacy reported in previous interventional trials [7,9], and is also very similar to that reported in the real-life VILDA study [8].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…However, data on HbA 1c were missing for a significant minority of patients, which means that these data should be interpreted with caution. The efficacy of sitagliptin observed in our study is similar to the efficacy reported in previous interventional trials [7,9], and is also very similar to that reported in the real-life VILDA study [8].…”
Section: Discussionsupporting
confidence: 91%
“…Another French observational study (VILDA) evaluated treatment maintenance with a different DPP-4 inhibitor, vildagliptin [8], with maintenance defined less stringently as discontinuation of vildagliptin. In that study, 11% of patients had discontinued vildagliptin after 2 years, a somewhat higher rate than that observed in our present study.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, patients treated with vildagliptin in addition to metformin exhibited no significant differences in the glycemic target achievement rates (HbA1c < 7%) in comparison with those treated with other active comparators [ 9 ]. Data from the VICTORY study are consistent with the key findings of these RCTs [ 9 ] and findings from previous real-life vildagliptin studies conducted in other regions [ 13 15 ]. The VICTORY study revealed that the mean reduction in HbA1c with vildagliptin as an add-on to metformin was −0.8% at the first follow-up visit at 12 weeks, which further improved to −1.0% at 24 weeks after treatment initiation.…”
Section: Discussionsupporting
confidence: 84%
“…Moreover, drug adherence is a critical factor to consider in the management of T2DM. The discontinuation of antidiabetic medication leads to a significant cost burden on the healthcare system and is frequently encountered in primary care patients [ 15 , 27 ]. Furthermore, patients with T2DM often have metabolic comorbid conditions such as hypertension and dyslipidemia [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…In another observational, 2-year prospective cohort study conducted in France, at the request of local health authorities, patients with type 2 diabetic mellitus initiating vildagliptin or treated for <6 months were recruited through a national representative sample of general practitioners (n=482) and diabetologists (n=84) between March 2010 and December 2011. 28 Of the 1700 patients included, vildagliptin treatment maintenance at 2 years was 88.8%; in everyday conditions of care, vildagliptin efficacy was in line with existing data from randomised clinical trials, sustained over 2 years, with low discontinuation rate and low hypoglycaemia risk. In a real-world analysis of administrative claims data from patients in the US, the predicted change in HbA1c from baseline equalled the results from head-to-head RCTs.…”
Section: Discussionsupporting
confidence: 64%